Pedagogical Efficacy of Guided Inquiry Modules: Enhancing Critical Thinking in Elementary Education Through Quasi-Experimental Validation - Uslan, Uslan; Binti Abdullah, Norazilawati; Aiman, Ummu; Yenni, Yenni (Universitas Muhammadiyah Surakarta, 2025)
The current research aims to examine the impact of guided inquiry-based learning on elementary school students' critical thinking. A quasi-experimental research design with one group pre-test and post-test was employed. The participants were 24 elementary school students selected based on the convenience sampling method. Pre and post-tests were given to the participants, and the data gathered was analysed through a paired sample t-test. The result of the paired sample t-test is significant with a p-value < .001, indicating the significant increase in the difference between the pre-test and post-test of the students' critical thinking. Other than that, the standard deviation of the difference is 10.60, with a standard error of 1.53, with the mean difference between posttest and pretest being 77.33 points, indicating the different result of the posttest with the pretest. Furthermore, the values 2.08 for Cohen’s d and 2.01 for Hedges’ correction indicate that the guided inquiry module had a strong and meaningful impact on enhancing students’ critical thinking abilities. In this case, the hedges and Cohen’s d value emphasise the significance of guided inquiry-based learning for the development of students’ critical thinking. Therefore, the current research confirms the significance of the use of guided inquiry-based learning to improve elementary school students' critical thinking.